Developing Digital Stories with Youth on Climate Change and HIV Vulnerabilities in Nairobi and Kisumu, Kenya: Methods and Reflections - Carmen H. Logie; Sarah Van Borek; Aryssa Hasham; Julia Kagunda; Humphres Evelia; Beldine Omondi; Arnold Asava; Maryline Okuto; Clara Gachoki; Mercy Chege; Mumbi Mwangi; Lesley Gittings (International Journal of Qualitative Methods, 2025)
There is a growing focus on the linkages between climate change and HIV vulnerabilities in Eastern and Southern Africa through pathways such as sexual and gender-based violence and transactional sex. Kenya is a relevant context to understand these linkages, with one of the world’s largest HIV epidemics and increasing climate-related extreme weather events (EWE) such as drought and flooding. Yet, the lived experiences of Kenyan youth at the nexus of climate change and HIV vulnerabilities remains understudied. Digital storytelling is a promising research approach that can meaningfully engage marginalized populations in sharing their experiences and generating solutions for stigmatized topics such as HIV prevention. Digital storytelling involves the creation of short audio-visual clips that combine personal storytelling with images, voice-over narration, and sound effects. This approach can also be used as tool for education, advocacy, and youth-centred knowledge production. We developed and implemented a digital storytelling video workshop methodology with youth aged 16–24 ( n = 54) in two Kenyan regions: informal settlements in Nairobi and fishing communities in Kisumu. The two-day digital storytelling workshops focused on: (1) providing information on climate change and its pathways to sexual health outcomes, including HIV; (2) building youth capacity to share their lived experiences and generate solutions through storytelling; (3) teaching audiovisual production skills; and (4) promoting advocacy, awareness, and peer education on HIV and climate change-related issues. This article describes the development and implementation of this methodology. Youth reflections on their experiences participating in these digital storytelling workshops identified the following themes: (1) new insights on HIV and climate change; (2) developing new skills; (3) building community connections; and (4) feeling more empowered. Findings reveal how digital storytelling methods can amplify youth voices and in turn generate new insights on the intersection of climate change and HIV in low- and middle-income contexts such as Kenya.